Construction of Waqf Ahli: Cash Waqf Management based on Family Economic Sustainability based at Roumah Wakaf Surabaya - Dikuraisyin, Basar; Hakim, Abdul (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2025)
This study analyzes the role of waqf experts in managing cash waqf for family economic security and developing a model for utilizing cash waqf based on economic independence. Cash waqf is used for public benefit, but its benefits are not felt by families and waqf experts. Cash waqf does not provide economic independence for mauquf alaih. This study uses a qualitative-analytical approach with a case study method through interviews with the chief executive and head of distribution at BAZNAS Gresik. The findings show that BAZNAS Gresik implements a hybrid management model that integrates productive waqf with the principles of social entrepreneurship, where cash waqf funds are channeled as revolving capital for family micro-enterprises. This approach increases income stability and reduces the economic vulnerability of mustahik families. This study resulted in the reconstruction of family-based waqf management by emphasizing the synergy between waqf sustainability and household economic resilience. In practical terms, this study confirms the role of zakat institutions in building an inclusive financial ecosystem through productive waqf. The study concludes that waqf construction experts serve as a transformative mechanism for achieving economic and social goals in modern Islamic philanthropy.